Evaluation of manipulators under CPPS frame. Issue 1 (July 2017) - Moulianitis, V.C.; Zachiotis, G.; Valsamos, C.; Aspragathos, N.A.
Abstract: In this paper, a method for evaluating robots as parts of a CPPS based on their abilities is presented. The relationship between the CPPS characteristics and robot abilities is determined. The minimum level of robot abilities is determined in order to have a positive influence on CPPS. The proposed mapping is used to evaluate the anatomy of three types of open chain robots: fixed anatomy, reconfigurable and metamorphic robots. Metamorphic robots, a class of modular open chain manipulators, are found to be better than the other two types. However, their superiority comes with increased complexity of the system.